Activation of the innate immune response and organ injury after cardiac surgery: a systematic review and meta-analysis of randomised trials and analysis of individual patient data from randomised and non-randomised studies. (September 2021) - Abbasciano, Riccardo G.; Lai, Florence Y.; Roman, Marius A.; Rizzello, Angelica; Pathak, Suraj; Ramzi, Joussi; Lucarelli, Carla; Layton, Georgia R.; Kumar, Tracy; Wozniak, Marcin J.; Eagle-Hemming, Bryony; Akowuah, Enoch; et al.
Abstract: Background: It is unclear whether the innate immune response represents a therapeutic target for organ protection strategies in cardiac surgery. Methods: A systematic review of trials of interventions targeting the inflammatory response to cardiac surgery reporting treatment effects on both innate immune system cytokines and organ injury was performed. The protocol was registered at the International Prospective Register of Systematic Reviews: CRD42020187239. Searches of the Cochrane Central Register of Controlled Trials, MEDLINE, and Embase were performed. Random-effects meta-analyses were used for the primary analysis. A separate analysis of individual patient data from six studies ( n =785) explored sources of heterogeneity for treatment effects on cytokine levels. Results: Searches to May 2020 identified 251 trials evaluating 24 interventions with 20 582 participants for inclusion. Most trials had important limitations. Methodological limitations of the included trials and heterogeneity of the treatment effects on cytokine levels between trials limited interpretation. The primary analysis demonstrated inconsistency in the direction of the treatment effects on innate immunity and organ failure or death between interventions. Analyses restricted to important subgroups or trials with fewer limitations showed similar results. Meta-regression, pooling available data from all trials, demonstrated no association between the direction of the treatment effects on inflammatory cytokines and organ injury or death. The analysis of individual patient data demonstrated heterogeneity in the association between the cytokine response and organ injury after cardiac surgery for people >75 yr old and those with some chronic diseases. Conclusions: The certainty of the evidence for a causal relationship between innate immune system activation and organ injury after cardiac surgery is low.